PENGARUH SUHU TERHADAP PEMIJAHAN KERANG MUTIARA Pinctada maxima (JAMESON) - Tomatala, Pitjont (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2011)
Pearl oysters, Pinctada maxima, are known as South Sea Pearl. Breeding is an important factor in intensive culture pearl oyster. In breeding, spawning became determining factor. The purpose of this research was to understand the effect of temperature decrease on the spawning level and to compare the treatment of water temperature decrease and increase on spawning level of pearl oyster P. maxima. The result showed that temperature decrease treatment influenced the success of the spawning level. Both water temperature decrease and increase had similar effect on the spawning level of the pearl oyster.